Analisis Rasio Keuangan Dalam Memprediksi Pertumbuhan Laba Pada Perusahaan Transportation Services Yang Terdaftar Di Bursa Efek Indonesia (Bei) Periode 2011- 2013 - Susanto, Ana (2016)
The purpose of this study 1) to determine the effect the current ratio (CR) effect on profit growth in transportation services company listed on the Indonesia Stock Exchange (BEI). 2) To determine the influence of Debt to Equality Ratio (DER) effect on profit growth in transportation services company listed on the Indonesia Stock Exchange (BEI). 3) To determine the effect Net Profit Margin (NPM) effect on profit growth in transportation services company listed on the Indonesia Stock Exchange (BEI). 4) To determine the influence of Total Asset Turnover (TAT) effect on profit growth in transportation services company listed on the Indonesia Stock Exchange (BEI). 5) To determine the effect Return On Asset (ROA) effect on profit growth in transportation services company listed on the Indonesia Stock Exchange (BEI). 6) To determine the influence of Return On Equity (ROE) effect on profit growth in transportation services company listed on the Indonesia Stock Exchange (BEI). Sampling was based on purposive sampling with criteria as follows: The Company Transportation Services listed in the Indonesia Stock Exchange and consistent over the period 2011 to 2013, providing a Transportation Services company financial statements during the period of the study in 2011 to 2013 and the company does not produce growth negative earnings during the period 2011 to 2013. Based on the above criteria the sample companies have 11 companies Based on the test results of the coefficient of determination (R2) obtained Adjusted R square (R2) of 0.868, indicating that the variation of profit growth can be explained by the variable CR, DER, NPM, TAT, ROA and ROE of 86.8%, while the rest in explain 13.2% influenced by other factors beyond the variables studied. Results of analysis together with using the F test, that the variables CR, DER, NPM, TAT, ROA and ROE significantly affect earnings growth, due to the significance value less than 0.05. Results of the analysis of the variables individually by using multiple linear regression, it is known that CR significant effect on earnings growth, variables DER no significant effect on earnings growth, variable NPM significant effect on earnings growth, the variable TAT significant effect on earnings growth, variable individually using multiple linear regression, it is known that the ROA no significant effect on earnings growth, ROE significant effect on earnings growth at the company's Transportation Service.